Association between Hormonal Contraceptive Use and Hypertension Risk among Reproductive-Age Women: A Cross-sectional Study at Cileungsi Public Health Center, Indonesia - Nafara Maharani Itamy, Defa; Rahmi, Eldiza Puji; Luthfiyani Citra Pradana, Dhigna; Farida Muti, Annisa (Universitas Ahmad Dahlan, 2025)
Hypertension remains a major public health problem that may be influenced by hormonal contraceptive use, particularly oral and injectable methods commonly used by women of reproductive age. These contraceptives have raised concerns about their potential impact on blood pressure regulation. This study aimed to investigate the association between hormonal contraceptive use and the occurrence of hypertension among women of reproductive age at the Cileungsi Public Health Centre, Bogor Regency, Indonesia. A cross-sectional study was conducted in 2024 using retrospectively collected medical record data of all hormonal contraceptive users at the facility. Total sampling was applied, and data on contraceptive type, duration of use, age, parity, and the most recent blood pressure readings were analyzed. The chi-square test was employed to examine associations between hormonal contraceptive characteristics and hypertension, with a significance level set at p < 0.05. The results revealed a significant association between contraceptive type and hypertension (p = 0.01, OR = 0.27), showing that users of oral contraceptive pills were more likely to develop hypertension than injectable users. Duration of use (p = 0.03, OR = 3.06), age (p = 0.04, OR = 0.12), and parity (p = 0.01, OR = 0.21) were also significantly associated with hypertension. Women aged ≥45 years, those with longer contraceptive use, and multiparous users exhibited a higher risk of elevated blood pressure. These findings highlight that both contraceptive-related and demographic factors contribute to hypertension risk among hormonal contraceptive users. Regular blood pressure monitoring and individualized counseling are essential, especially for oral and long-term users. This study contributes local evidence supporting safer contraceptive practices and cardiovascular risk management within primary healthcare settings.